Basic Discussions about the Study of Education-Work Relationship in Argentina - Vicente, María Eugenia (2017)
Employee training makes it possible to improve the working and relational practices, and thus, secure social, professional and personal promotion in the framework of the productivity of regional and local economy. The aim of this article is to provide relevant background to the study of the relationship between education and work, and especially, employee training. Six main discussion points about education and work are recognized in the specialized literature. Although the discussions come mostly from the Argentinean field of study, they are relevant to take into account in all research background on the topic.